Analisis Kekuatan Bending Akibat Variasi Arus Pengelasan SMAW Pada Sambungan Pipa Api 5L GR.B SCH 80 - Aditya Rizky Dwicahya; Okik Hendriyanto Cahyonugroho (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
In this research, we use experimental research to determine the characteristics of a material, namely API 5L Grade B sch 80 pipe, using variations in welding current using SMAW (Shielded Metal Arc Welding) welding to determine the effect of variations in SMAW welding current on the value of liquid penetrant test results, radiographic test and mechanical properties of bending tests on API 5L Grade B sch 80 pipe material. It can be concluded that welding with variations in current strength of 80 A gives an average value of 396.381 MPa from the bending test results. Meanwhile, when the current variation is 100 A, it is known that the result of the current variation of 100 A is 652.315 MPa. It is known that when the amperage is varied by 120 A, the value of the bending test results is smaller than when the amperage is varied by 80 A, and when the amperage is varied by 100 A, the average value of the amperage variation by 12 A is 286.744 MPa. In conclusion, since there are no defects in this liquid penetrant test that could be dangerous or cause leakage, the welding results can be used or continued. There are deficiencies in the test results, but the NDT inspector with certification number SNS/PT/RN-23008 can still approve them